2021
DOI: 10.5772/intechopen.96451
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol: An Underrated Isomer of Vitamin E in Health and Diseases

Abstract: Vitamin E was first discovered as a fertility factor in 1922 in the laboratory of Herbert McLean Evans, a scientist and anatomist. Following this discovery, it was extensively researched and found to possess a potent antioxidant property. It soon dawned that the family of vitamin E has eight members: four tocopherols, namely α-, β-, δ- and γ-tocopherol; and four tocotrienols in the form of α-, β-, δ- and γ-tocotrienols. This chapter discusses this rather unknown and underrated isomer of vitamin E with unsurpas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 231 publications
(209 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that daily oral tocotrienol intake protected against ovariectomy-induced bone changes in rat models ( Mohamad et al, 2012 ; Soelaiman et al, 2012 ; Muhammad et al, 2013 ; Chin et al, 2017 ). All these studies suggested that tocotrienol protected the bone by increasing osteoblast number, mineral deposition, and bone formation, as well as reducing osteoclast number to prevent bone resorption, erosion, and degeneration of bone mineral density and microarchitecture ( Musa, 2021 ). However, tocotrienol was associated with limited oral bioavailability as they were not recognized by the alpha-tocopherol transfer protein for intake into the body ( Packer et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that daily oral tocotrienol intake protected against ovariectomy-induced bone changes in rat models ( Mohamad et al, 2012 ; Soelaiman et al, 2012 ; Muhammad et al, 2013 ; Chin et al, 2017 ). All these studies suggested that tocotrienol protected the bone by increasing osteoblast number, mineral deposition, and bone formation, as well as reducing osteoclast number to prevent bone resorption, erosion, and degeneration of bone mineral density and microarchitecture ( Musa, 2021 ). However, tocotrienol was associated with limited oral bioavailability as they were not recognized by the alpha-tocopherol transfer protein for intake into the body ( Packer et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%